Translating Bhagavad in Diverse Context: a Chinese-Indonesian Account (Paramita: Historical Studies Journal, 2016)
Bhagavad-Gita has continuously been translated and distributed in some Indonesian regions, especially in Java and Bali. It has religiously been read not only by Hindu people community, but mostly discussed by Theosophical society and Javanese aliran kebatinan people. This paper aims to analyze two translated versions of Bhagavad-Gita written by Kwee Tek Hoay (KTH), which was translated in Indonesian language Bhagavad Gita Interpreted (1960) and in Javanese one Handaran Bhagavad-Gita (1960). KTH confidently claims that he used Bhagavat-Gita Interpreted in the Light of Christian Tradition(1923) as a source of translation. This paper investigates how “spiritual” salient concepts was translated, transformed and contested in the context of Chinese-Indonesian and Javanese terms. This paper concludes that the passion of KTH translocality translation has been a representative of fluid religious identity which constitutes a specific worldview of Indonesian society as an inspiration source of spirituality.Bhagavad-Gita terus menerus telah diterjemahkan dan didistribusikan di beberapa daerah Indonesia, terutama di Jawa dan Bali. Dalam konteks keagamaan, naskah ini telah dibaca tidak hanya oleh masyarakat orang Hindu, tapi sebagian besar dibahas oleh masyarakat penganut mistik dan aliran kebatinan Jawa. Tulisan ini bertujuan untuk menganalisis dua versi terjemahan dari Bhagavad-Gita yang ditulis oleh Kwee Tek Hoay (KTH), yang diterjemahkan dalam bahasa Indonesia tahun 1960 dan juga Handaran Bhagavad-Gita (1960). KTH percaya diri mengklaim bahwa ia menggunakan Bhagavat-Gita Interpreted in the Light of Christian Tradition (1923) sebagai sumber terjemahan. Tulisan ini menyelidiki bagaimana konsep "spiritual" yang menonjol diterjemahkan, diubah dan diperebutkan dalam konteks istilah Cina-Indonesia dan Jawa. Makalah ini menyimpulkan bahwa gairah terjemahan KTH telah menjadi perwakilan dari identitas agama yang merupakan pandangan dunia tertentu masyarakat Indonesia sebagai sumber inspirasi dari spiritualitas.